Corrupción en arbitraje internacional de inversiones: ¿es un peligro o un salvavidas para países en desarrollo? - Alvarez Calderón Campos, Andrés (2020)
In recent years, corruption allegations in investment arbitration have increased considerably. When raised by the States, said allegations are intended to pursue the dismissal of the claims due to lack of jurisdiction of the arbitral tribunals, based on the existence of corruption throughout the investment. Nevertheless, there is no consensus in the criteria used by tribunals, given that the involvement of the State in the corrupt acts may play a significant role in the decision. In this article, the author discusses the main defense arguments used by States when alleging the existence of corruption and presents the various criteria applied by investment tribunals to deal with such allegations. In addition, the author proposes a test that tribunals may apply to decide on the effect these allegations have on the arbitration proceedings.